A cross‐sectional study of fluency and reading comprehension in Spanish primary school children. (17th December 2013) - Calet, Nuria; Gutiérrez‐Palma, Nicolás; Defior, Sylvia
<x xml:space="preserve">Abstract</x> The importance of prosodic elements is recognised in most definitions of fluency. Although speed and accuracy have been typically considered the constituents of reading fluency, prosody is emerging as an additional component. The relevance of prosody in comprehension is increasingly recognised in the latest studies. The purpose of this research is to examine the contribution of prosodic reading to comprehension beyond automaticity in word reading, taking into account children's grade level. One hundred and twenty‐two Spanish children (74 second and 48 fourth graders) were tested in prosodic reading, automaticity in word reading (nonword reading and reading rate) and comprehension abilities. Results show that the contribution of automaticity in word reading is relevant in both grades; however, it is more significant in Grade 2. The prosodic components of reading seem to be related differently to comprehension across grades, intonation being the highest predictor of comprehension in Grade 4. Implications for educational practice are discussed.